Phytosanitary monitoring of the narrow-leaved lupine collection of VIR in the northwest of Russia - R. A. Abdullaev; M. A. Vishnyakova; G. P. Egorova; E. E. Radchenko (Труды по прикладной ботанике, генетике и селекции)
Background. Narrow-leaved lupine (Lupinus angustifolius L.) is an important high-protein forage and green manure crop, also promising for food use. This is a plastic species produced under various ecogeographic conditions and the only cultivated species of lupine adapted to high northern latitudes – up to 60° NL. Gradual expansion of lupine production areas led to the accumulation of pathogens, damage to lupine crops by harmful organisms, and significant harvest losses. Breeding and cultivating resistant varieties is the most profitable and environmentally sound way to control diseases and pests. Studying the species composition of pathogens and searching for source material are the necessary stages of plant breeding for immunity.Materials and methods. A set of 101 accessions of L. angustifolius from the VIR collection were studied in the northwest of the Russian Federation (Pushkin, St. Petersburg) in 2019, and 62 accessions from the same set in 2020. Mycological examination of the affected leaves was carried out on potato sucrose agar medium under laboratory conditions. The degree of damage to plants by diseases and infestation by pests was assessed during the period of flowering, fruit formation and ripening using point scales.Results and conclusions. A wide range of harmful organisms were identified for their negative impact on the growth and development of narrow-leaved lupine plants. The dominant pest was the lupine aphid (Macrosiphum albifrons Essig), discovered in Russia for the first time. A whole set of fungal pathogens was identified, among which the most common and harmful were the causative agents of Fusarium, brown leaf spot, powdery mildew, gray mold, and Sclerotinia stem rot. Narrow-leaved lupine accessions with weak degrees of pathogenic damage were selected.